2020
DOI: 10.1038/s41598-020-65749-9
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of organic manure and potassium forms on maize (Zea mays L.) growth and production

Abstract: Worldwide, maize (Zea mays L.) is considered an important food and fodder crop. compost as a soil amendment and potassium (K) could enhance the maize yield. Therefore, two field experiments were carried out in the two seasons 2017 and 2018 to study the effects of compost at three levels and four forms of potassium fertilization on the yellow maize hybrid 'Pioneer Sc 30N11' yield components. to conduct the field trials, a split plot system in three replications was established. Three compost levels (0, 5 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 40 publications
3
48
1
3
Order By: Relevance
“…The increase of these characters may be due to the role of organic manure for the physiological and productivity of barley. These findings are in the same line with those obtained by Rudrappa et al (2006), Schmidt et al (2011); Gomaa et al (2015); Gomaa et al (2020); Kandil et al (2020) they reported that organic manure had a vital role for improving soil properties, increasing essential macronutrients, increasing micronutrients availability, and increasing crop yield.…”
Section: Resultssupporting
confidence: 89%
“…The increase of these characters may be due to the role of organic manure for the physiological and productivity of barley. These findings are in the same line with those obtained by Rudrappa et al (2006), Schmidt et al (2011); Gomaa et al (2015); Gomaa et al (2020); Kandil et al (2020) they reported that organic manure had a vital role for improving soil properties, increasing essential macronutrients, increasing micronutrients availability, and increasing crop yield.…”
Section: Resultssupporting
confidence: 89%
“…The number of observed species was highest in D40N.S samples at 2449. 25 In addition, a trend was found that the diversity of bacterial communities declined in most inoculant-applying treatments in the different nitrogen application rate groups, compared with their own control (CF, D20N, and D40N) in the corresponding groups. Two exceptions were discovered: one was CF.M in the CF group, and the other was D40N.S in the D40N group, whose diversity of bacterial communities was enhanced by Inoculant M and Inoculant S, respectively.…”
Section: Alpha Diversitymentioning
confidence: 93%
“…In this study, the effects of different microbial inoculants (including one made of bacterial strains that were screened in our lab, and two commercial inoculants) on bacterial communities of rhizosphere soil were investigated. To carry out our research conveniently, maize (Zea mays L.) was selected as our experimental crop because it is one of the most important food crops, ranked third in the list of the top three cereal crops in the world, besides wheat and rice [25]. Maize is widely planted in Central America, Mexico, Africa, and northeastern China, accounting for 94% of all cereal crop consumption along with wheat and rice, which satisfies the vast need for nutrients and nearly half the caloric requirement of humankind [26].…”
Section: Introductionmentioning
confidence: 99%
“…Si may work as a growth regulator and has the potential to increase plant growth under drought stress 27 . The growth and yield of maize were highly responsive to Si application under stressed conditions 5,28 . Spraying K-silicate and other nanomaterials has the potential to reduce the harmful effects of drought stress on crops [29][30][31][32] .…”
mentioning
confidence: 99%